2016
DOI: 10.3402/gha.v9.33194
|View full text |Cite
|
Sign up to set email alerts
|

The performance of community health workers in the management of multiple childhood infectious diseases in Lira, northern Uganda – a mixed methods cross-sectional study

Abstract: BackgroundCommunity health workers (CHWs) have the potential to reduce child mortality by improving access to care, especially in remote areas. Uganda has one of the highest child mortality rates globally. Moreover, rural areas bear the highest proportion of this burden. The optimal performance of CHWs is critical. In this study, we assess the performance of CHWs in managing malaria, pneumonia, and diarrhea in the rural district of Lira, in northern Uganda.DesignsA cross-sectional mixed methods study was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 22 publications
(25 reference statements)
5
35
0
Order By: Relevance
“…Guidelines produced by the The United States Agency for International Development (USAID) Health Care Improvement Project recommend that refresher training should be provided at least every 6 months to update CHWs on new skills, reinforce initial training and ensure they are practising skills learnt, 16 yet some CHWs have not had refresher training for over 5 years. 17 This finding of a poor provision of ongoing training is commonplace and mentioned in several other studies, across multiple geographic contexts. 18–21 A multinational analysis from several countries in sub-Saharan Africa concluded that the current provision of refresher training courses was ‘not sufficient to meaningfully improve the quality of care in these countries’, raising into question the need to assess the effectiveness of training programmes, both from the perspective of the individual CHW and the health system in which they operate.…”
Section: Introductionmentioning
confidence: 70%
“…Guidelines produced by the The United States Agency for International Development (USAID) Health Care Improvement Project recommend that refresher training should be provided at least every 6 months to update CHWs on new skills, reinforce initial training and ensure they are practising skills learnt, 16 yet some CHWs have not had refresher training for over 5 years. 17 This finding of a poor provision of ongoing training is commonplace and mentioned in several other studies, across multiple geographic contexts. 18–21 A multinational analysis from several countries in sub-Saharan Africa concluded that the current provision of refresher training courses was ‘not sufficient to meaningfully improve the quality of care in these countries’, raising into question the need to assess the effectiveness of training programmes, both from the perspective of the individual CHW and the health system in which they operate.…”
Section: Introductionmentioning
confidence: 70%
“…A total of 16 studies are included in this review, 5 of which were from East Africa, 4 from Central Africa, 3 from West Africa, and 4 from Southern Africa. Countries represented were Uganda with four studies [ 11 14 ], Kenya with three [ 15 17 ], one from Rwanda [ 18 ], one from Tanzania [ 19 ], one from Burkina Faso [ 20 ], one from Ghana [ 21 ], one from Mali [ 22 ], one from Malawi [ 23 ], and three from Zambia [ 24 27 ]. Twelve of the studies had a cross-sectional design [ 11 – 18 , 20 , 22 , 23 , 25 ], one was a mixed methods prospective study [ 24 ], one was a cluster randomized control trial [ 26 ], one was a randomized crossover trial [ 22 ], and one randomized control stepped wedge trial [ 21 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The progress is significant even though the baselines are already quite high and margins for progress are naturally limited. Research suggests that the capacities of community health workers tend to wane rather quickly [11,23,24] and that refresher training effectively enhances their performance [12,25,26]. The CBDs of the 2017 and 2018 campaigns thus seemed to have benefited from the cumulative contribution of each initial campaign training session, the supervision provided by the health teams during each round, and the regular refresher training preceding each round.…”
Section: Discussionmentioning
confidence: 99%